Current-status and applications of polysaccharides in drug delivery systems - Prasher, Parteek; Sharma, Mousmee; Mehta, Meenu; Satija, Saurabh; Aljabali, Alaa A.; Tambuwala, Murtaza M.; Anand, Krishnan; Sharma, Nitin; Dureja, Harish; Jha, Niraj Kumar; Gupta, Gaurav; Gulati, Monica; et al. (Colloid and interface science communications, 2021)
The polysaccharide-based advanced drug delivery system owing to their biocompatibility, ability to encapsulate the drug molecules in their interspaces, and ability to achieve a controlled release of the cargo drug molecules result in improved drug pharmacokinetics. The drug-loaded polysaccharides possess ability to evade the multidrug-resistant microbial efflux pumps by aggregation effect, whereas the drug loaded polysaccharide-fabricated metal nanoparticles present an exceptional candidature for effectively transporting the drug molecules across the membrane barriers while enabling the theranostic applications at the same time. The biodegradability of polysaccharide based drug delivery systems ensure a sustained release of the encapsulated drug molecules, which minimizes the side effects caused by a burst release of the cargo therapeutics. These drug delivery systems proved highly beneficial for the NSAIDs that otherwise manifest ulcerogenic effect in the gastrointestinal tract. The large surface area of polysaccharides further provide a higher drug-loading capacity, which maintains the optimal concentration of the cargo drug at the target sites. The emerging applications of biodegradable polysaccharides in the designing of multicompartmental microspheres revolutionized tissue engineering, multi drug delivery, and cell culturing technologies. The present review deals with the current-status of polysaccharides as advanced drug delivery systems. [Display omitted] •Nature of polysaccharide-drug interactions•Factors influencing the drug delivery by polysaccharides•Advanced drug delivery applications of polysaccharides